Analysis of Water Quality in Traditional Oil Mining Using the Pollution Index Method in Gampong Alue Peuno - Muchlis; Nurul Aflah; Amelia; Lubis, Mirna (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Gampong Alue Peuno, Bireuen, us a region in Aceh known for its rich petroleum resources. This abundance has led to many oil wells being freely managed by the local community. This study aims to analyze water quality in Gampong Alue Peuno according to established water quality standards, utilizing the Pollution Index method in reference to the Indonesian Minister of Environment Decree No. 115 of 2003. The Pollution Index assesses water quality across ten points, considering parameters such as pH, temperature, oil and fat, TDS, BOD, COD, and DO. Water quality calculations for Gampong Alue Peuno yielded Pollution Index (IP) values at points 1 through 10 of 2.423, 3.505, 2.022, 2.534, 2.241, 2.328, 1.847, 3.180, 4.370, 1nd 1.510, respectively. Based on Decree No. 115 of 2003, all teat points fall into the light pollution category (1.0 < IP < 5.0 for Class II water quality standards. Water in Class II with light pollution is not recommended for daily activities such as washing dishes, washing clothes, bathing, irrigating plants, and livestock care, or other needs requiring similar water quality. Polluted water usage can directly or indirectly affect public health and harm aquatic ecosystems.